The elite connection problems and potential of Western democracy - Etzioni-Halevy, Eva. (Cambridge Polity Press, 1993)
Designed as a textbook for courses in political theory, political sociology and comparative politics, and as a contribution in its own right, this book explores the role of elite relations as a key to understanding democracy.
Includes bibliographical references (p. [218]-232) and index.
Keywords: Democracy